HOTEL MANAGEMENT STUDENTS INTERNSHIP SATISFACTION : THE CHALLENGE INVESTIGATION IN HOTEL - Saharani Yarietsa; Andrika Aldi; Yuspita Mardiana; Feri Ferdian (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to analyze the effect of individual challenges and organizational challenges on the satisfaction of hotel management student internships. The methodology used in this research is quantitative with a causal associative approach. Samples were selected using stratified random sampling. Hospitality management students in 2019, 2020 and 2021 are the population in this study. The number of samples in this study were 82 people who had done internships or were doing internships. The independent variable in this study is individual challenges and organizational challenges and the dependent variable is Internship satisfaction. The method used in this study is quantitative using two data analysis techniques, namely descriptive statistical analysis techniques to identify and describe data from the answers to the respondent's questionnaire and inferential statistical analysis techniques using the SEM (structural equation modeling) data analysis method using PLS (partial least square) approach. SmartPLS Application 3. The results showed that individual challenges did not affect hotel management student internship satisfaction. meanwhile Organizational challenges affect the satisfaction of hotel management student internships